The use of Sabetha Cartoons Animated Videos as Learning Media to Train Chinese Vocabulary for Students of The Chinese Language Education Study Program State University of Malang - Albinpa, Chairunisa Simfoni; Ventivani, Aiga; Retnantiti, Sawitri (Journal of Maobi, 2025)
This study aims to describe students activity when using Sabetha Cartoons animated videos as learning media to train Chinese vocabulary of students of Mandarin Language Education Study Program, State University of Malang and describe student responses to the use of these animated videos. This research uses a descriptive qualitative approach. The data source of this research is 33 students of the Chinese Language Education Study Program, State University of Malang class of 2023 whom had never learn Chinese lesson before. Data collection techniques used observation sheet instruments and questionnaires. The results of this study indicate that the use of Sabetha Cartoons animated videos is going well. Based on the results of the study, students felt more happy and interested in participating in learning using this media, although there were some students who experienced problems when using the animated video, namely, the pronunciation was too fast and there were some new vocabulary that had never been learned before. Students stated that Sabetha Cartoons animated video media can help them to practice Chinese vocabulary that is good and correct so that they can understand the contents of the Sabetha Cartoons animated video.